GREEN FINANCING IN THE PERSPECTIVE OF FINANCIAL PERFORMANCE: EMPIRICAL EVIDENCES FROM BANKING SECTOR IN INDONESIA (2019-2024) - Cindy Yoel Tanesia; Cherilyn Cristine Tompo; Monalisa (Accounting Profession Journal (APAJI), 2026)
This study aims to analyze the impact of green financing on financial performance and firm value in Indonesia's banking sector from 2019 to 2024. Using a quantitative method, the research examines the relationships between green financing, credit risk (LLP), profitability (ROE), and firm value (Tobin’s Q). The results indicate that green financing positively influences profitability and firm value, despite potential increases in credit risk due to green project complexity. These findings confirm that integrating environmental aspects strengthens reputation, attracts investors, and supports national economic sustainability.